2018
DOI: 10.1111/ejh.13033
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of PD‐L1 and PD‐L2 in classical Hodgkin lymphoma, primary mediastinal large B‐cell lymphoma, and gray zone lymphoma

Abstract: We identified increased staining of PD-L1 in cHL and that of PD-L2 in PMBL. GZL had a pattern similar to that of cHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…To our knowledge, this is the first study to report neoplastic expression of PD‐L1, and its correlation with pathological findings (i.e., anatomical position), in two cases of mediastinal composite lymphoma of NSCHL and PMBL. Several authors recently reported PD‐L1 expression on neoplastic cells in NSCHL, PMBL and MGZL; generally finding that the positive percentages were highest in NSCHL, lowest in PMBL, and intermediate in MGZL . Accordingly, in our control series, nPD‐L1 expression was observed in 100% of NSCHL (n = 7) and 18% of PMBL (n = 11).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…To our knowledge, this is the first study to report neoplastic expression of PD‐L1, and its correlation with pathological findings (i.e., anatomical position), in two cases of mediastinal composite lymphoma of NSCHL and PMBL. Several authors recently reported PD‐L1 expression on neoplastic cells in NSCHL, PMBL and MGZL; generally finding that the positive percentages were highest in NSCHL, lowest in PMBL, and intermediate in MGZL . Accordingly, in our control series, nPD‐L1 expression was observed in 100% of NSCHL (n = 7) and 18% of PMBL (n = 11).…”
Section: Discussionsupporting
confidence: 62%
“…Investigation of various markers have resulted in few consensus panels . Notably, CD274/programmed cell death ligand 1 (PD‐L1) positivity on tumor cells is characteristic of CHL, and is less frequently exhibited by PMBL . This suggests that PMBL may be divided into PD‐L1‐positive and ‐negative subgroups that are not yet well‐defined.…”
Section: Introductionmentioning
confidence: 99%
“…PD‐L2 expression was even present in some cases with missing PD‐L1 expression . In other malignancies such as primary mediastinal large B‐cell lymphoma and colorectal cancer, an increase in PD‐L2 expression and a negative prognostic value was also shown. This outlines the potential relevance of PD‐L2 expression as inhibitory immune checkpoint.…”
Section: Discussionmentioning
confidence: 96%
“…The same is true for lymphomas. [106][107][108][109][110][111] Development of multiple myeloma is also supported by essentially the same cell logistics, [112][113][114][115][116][117] and this seems to apply to sarcomas too. [118][119][120][121][122][123] The shared group of functional properties at issue here is in fact a subset of the currently recognized hallmarks of cancer.…”
Section: Related Specific Regulationmentioning
confidence: 97%